2020
DOI: 10.1002/ejhf.2044
|View full text |Cite
|
Sign up to set email alerts
|

In‐hospital care in acute heart failure during the COVID‐19 pandemic: insights from the German‐wide Helios hospital network

Abstract: Aims The coronavirus disease 2019 (COVID‐19) pandemic has led to changes in health care utilization for different acute cardiovascular diseases. Whether hospitalization rates and in‐hospital mortality were affected by the pandemic in patients with acute symptomatic heart failure (HF) was investigated in this study. Methods and results Administrative data provided by 67 German Helios hospitals were examined for patients with a main discharge diagnosis of HF using ICD codes. Urgent hospital admissions per day we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 45 publications
8
71
0
1
Order By: Relevance
“…The observed changes of in-hospital mortality during the pandemic are of interest but a detailed analysis of this observation is beyond the scope of the present study. Nevertheless, a previous study from our group that focussed on heart failure care has shown an association between increased case severity during the pandemic and in-hospital mortality [14].…”
Section: Limitationsmentioning
confidence: 84%
“…The observed changes of in-hospital mortality during the pandemic are of interest but a detailed analysis of this observation is beyond the scope of the present study. Nevertheless, a previous study from our group that focussed on heart failure care has shown an association between increased case severity during the pandemic and in-hospital mortality [14].…”
Section: Limitationsmentioning
confidence: 84%
“…During the course of the COVID‐19 pandemic, reduced hospitalization rates were described for multiple acute cardiovascular and non‐cardiovascular diseases 1‐14 . Since most of the previous investigations focused on the early phase of the pandemic in spring 2020, data concerning the development of hospitalization rates following April 2020 are scarce 15‐18 . Evidence of an increased case‐severity respective mortality, especially in patients with cardiovascular diseases, led to concern that those reduced treatment numbers could negatively affect patients' long‐term outcome 9,15,19 .…”
Section: Introductionmentioning
confidence: 99%
“…The Helios hospital group is the largest hospital network in Germany serving about 7% of the German population. We have established a continuous surveillance program to monitor and report the effects of the Covid-19 pandemic on hospital admissions, resource use and outcomes [ [6] , [7] , [8] , [9] , [10] ]. With this correspondence, we wish to complement this discussion by providing hospitalization, treatment and in-hospital outcome data for pulmonary embolism during the 2020 Covid-19 pandemic and a corresponding 2016–2019 control period.…”
mentioning
confidence: 99%